The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1563/aaid-joi-d-16-00195
|View full text |Cite
|
Sign up to set email alerts
|

Facial Alveolar Bone Width at the First and Second Maxillary Premolars in Healthy Patients: A Cone Beam Computed Tomography Study

Abstract: The purpose of this study was to analyze the thickness of the facial alveolar bone at the first and second maxillary premolars and determinate the percentage of premolars that reached 2 mm in width. A retrospective study was performed, analyzing cone beam computed tomography scans from the database of the Oral Surgery Unit of the University of Valencia. Patients with periodontal disease, orthodontic treatment, absence among the first maxillary molars, premolars with endodontic treatment, or prosthetic restorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…For the upper canines, 58 and 56% of first premolars showed a thickness thinner than 1 mm. Our results are in agreement with those of Rojo et al [ 30 ]. They show that the thickness of the first premolars seems to be less than that of second premolars, although our mean values were lower.…”
Section: Discussionsupporting
confidence: 94%
“…For the upper canines, 58 and 56% of first premolars showed a thickness thinner than 1 mm. Our results are in agreement with those of Rojo et al [ 30 ]. They show that the thickness of the first premolars seems to be less than that of second premolars, although our mean values were lower.…”
Section: Discussionsupporting
confidence: 94%
“…Authors (4,12) who have measured anterior and posterior areas have reported a significant increase in FAB thickness from incisors to premolars. In a previous study, we also observed that first premolars had significant greater FAB thickness than second premolars (19). Another factor to take into account when analyzing the anatomy of the alveolar process at maxillary anterior teeth, is the relation between the angulation of the root axis and the basal bone.…”
Section: Discussionsupporting
confidence: 61%
“…The measurements from the CEJ to the FBC and of the thickness of the FAB were performed at the sagittal plane (Fig. 1b) as reported by Rojo-Sanchis et al (19) For additional analysis, the subjects were divided into 3 groups according to the CEJ-FBC distance (Shorter group: ≤ 3 mm; Middle group: >3 and ≤ 4.5 mm; Larger group: > 4.5 mm) ( Table 1). Physiological bone levels range from 1 to 3 mm apical to the CEJ (20,21) (Shorter group); Middle and Larger groups correspond to teeth that had slightly or great loss of periodontal attachment.…”
Section: Methodsmentioning
confidence: 99%
“…First, the narrowness of the alveolar ridge in the area of the maxillary premolars makes it difficult to determine the bucco-palatal position of the implant fixture. 12 , 13 , 14 In addition, the alveolar ridge in the maxillary premolar area has a large buccal inclination that could restrict the angle of the implant fixture. 15 If the position and angle of the implant fixture does not take into consideration the alveolar bone morphology and inclination, fenestration and dehiscence could occur.…”
Section: Introductionmentioning
confidence: 99%